Laparoscopic Appendectomy: A Report on 1164 Operations at a Single-Institution, Safety-Net Hospital. Issue 6 (June 2018) - Dumas, Ryan P.; Subramanian, Madhu; Hodgman, Erica; Arevalo, Michelle; Nguyen, Gabriella; Li, Kevin; Aijwe, Tochi; Williams, Brian; Eastman, Alexander; Luk, Stephen; Minshall, Christian; Cripps, Michaelw
Laparoscopic appendectomy (LA) is the standard of care for the treatment of acute appendicitis. There is an ongoing debate regarding the optimal management of appendicitis, which led us to study outcomes after an appendectomy at a large safety-net hospital. We hypothesize that despite a high-risk population, LA remains a safe and effective treatment for acute appendicitis. A retrospective review was performed of all patients who underwent an appendectomy from 2011 to 2013. The primary end point was significant morbidity defined as a score of three or greater on the Clavien-Dindo scale of surgical morbidity. Thousand hundred and sixty-four patients underwent an appendectomy. A total of 1102 (94.7%) patients underwent either an LA or laparoscopic converted to open appendectomy, and 62 (5.3%) patients underwent an open appendectomy (OA). Two hundred and forty six patients (21.1%) had complicated appendicitis. Laparoscopic converted to OA conversion rate was 4.4 per cent and differed between years (P < 0.001). LA had a significantly shorter length of stay, shorter length of postoperative antibiotics, and less postoperative morbidity. When limited to only patients with complicated appendicitis, major morbidity was still greater in the OA group (22.6 vs 52.0%, P = 0.001). Length of stay was significantly longer in the OA group [3.42 (2.01, 5.97) vs 7.04 (5.05, 10.13), P < 0.001]. Odds for complication were 2.6 times greater in the OA group compared with the LA group. In the absence of peritonitis and systemic illness necessitating urgent laparotomy, patients who are laparoscopic surgical candidates should be offered an LA. Our study demonstrates that these patients have better outcomes and shorter hospital stays.